Satisfaction Level of BPJS Kesehatan Participants Using the C4.5 Algorithm - Irvan Okta Mazhona; Yuhandri (SYSTEMATICS, 2020)
Patient satisfaction is an important thing in a hospital service. The level of patient satisfaction can be a reference for improving service to patients. Satisfaction is the level of feelings that arise as a result of the performance of the service received after comparing it with what is expected. This study aims to measure the level of satisfaction of inpatient BPJS Kesehatan participants with the services provided by the Special Hospital for Mother and Children (RSKIA) Annisa Payakumbuh in terms of five attributes, namely Tangibles (Real Form), Reliability, Assurance, Responsiveness (Responsiveness) and Empathy (Empathy). To measure the level of patient satisfaction at RSKIA Annisa Payakumbuh used data mining method of Classification Algorithm C4.5 which is one of the most effective Decision tree algorithms for classification. The data were obtained from the summary of the results of the BPJS Kesehatan inpatient patient satisfaction survey at RSKIA Annisa Payakumbuh. Furthermore, the data will be processed using the C4.5 algorithm which will produce rules and Decision trees. The results of data processing using the C4.5 Algorithm obtained Responsiveness as the root variable and resulted in 8 rules with 3 satisfied rules and 5 unsatisfied rules. Based on the results of this study, it can be concluded that the use of the C 4.5 Algorithm Decision tree can be used to measure the level of satisfaction of BPJS Kesehatan inpatients at RSKIA Annisa Payakumbuh. The results of this study are expected to help the RSKIA Annisa in making policies to improve services for patients.